DEVELOPMENT OF THE PETROCHEMICAL INDUSTRY OF THE KINGDOM OF BAHRAIN - Aidrous, I.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Ėkonomika, 2017)
Gulf monarchies started developing petrochemical industry in 1980-s. During a quarter of a century they have become the regional and global hub for the petrochemical production. Petrochemicals besides the refining industry are considered to be of the main priorities for the economic development of Bahrain. Export activities, corporate management, products quality, environmental protection of the key company GPIC contribute not only to the GDP growth but to the strengthening of competitiveness of Bahrain in the international market for such petrochemical products as ammonia, methanol and urea and its economy.